FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT MACET PADA KOPERASI SERBA USAHA SOLATA - Ratnasari Manggu, Sri Astuty (EDUTECH CONSULTANT, 2019)
This study aims to determine the factors that affect bad credit at the Cooperative, which specifically examines the problem of bad credit experienced by the Solata Cooperative Cooperative in West Sulawesi which is increasing. these factors are limited to three variables, namely: loan interest rates, credit collectibility and accounts receivable turnover. This study uses multiple regression analysis techniques to determine the effect of factors that influence bad credit in the Solata Cooperative. The results showed that, of the three factors that had a significant influence only the credit collectibility value, with a significance level of 0.024. Meanwhile, the interest rate and receivable turnover factors have no effect on bad credit at the Solata Multipurpose Cooperative.